Validity of Broselow tape for estimating the weight of children in pediatric emergency: A cross-sectional study - Zhu, Shuzhen; Zhu, Jihua; Zhou, Hongqin; Chen, Xiuping; Liang, Jianfeng; Liu, Lijun; Zhang, Caidi; Zhao, Yingying; Chen, Yanyan; Wu, Xiao; Ye, Sheng; Jiang, Kewen (Frontiers in Pediatrics, 2022)
Objective To assess the validity of the Broselow tape in estimating the weight of Chinese children in pediatric emergency. Methods A cross-sectional study was conducted in the emergency department of the Children's Hospital of Zhejiang University School of Medicine (Hangzhou, Zhejiang Province, China) in March 2022. Broselow tape was used to estimate weight and its validity was compared with the advanced child life support (APLS) method. Results The study included 442 children (mean age: 48 months; male-to-female ratio: 1.13:1). The < 10, 10–19 and > 19-kg groups included 44, 257, and 141 children, respectively. The color concordance rates of the Broselow tape-estimated weight in the three groups were 56.8, 57.2, and 68.1%, respectively. The percentage of weight estimations within 10% of actual weight were 65.8% (59.1, 65.8, and 68.1% for the <10, 10–19 and > 19-kg groups, respectively) and 44.8% (40.9, 50.6, and 35.5% for the < 10, 10–19 and > 19-kg groups, respectively) using the Broselow tape and the APLS method, respectively. The correlation between the Broselow tape estimated weight and actual weight was r = 0.931 (P < 0.0001, 95% CI: 0.918–0.943), while the correlation between actual weight and the APLS method calculated weight was r = 0.883 (P < 0.0001, 95% CI: 0.861–0.902). The mean percentage error using the Broselow tape was 1.0 ± 12.0% (P < 0.001 vs. −7.2 ± 17.2% of the APLS method). Conclusion The Broselow tape may be an available method for predicting the weights of Chinese children in pediatric emergency.